ANALYSIS OF THE RELATIONSHIP BETWEEN THE BEHAVIOR OF IMPLEMENTING NURSES TO FILLING OUT THE DAILY CENSUS OF INPATIENTS AT THE HOSPITAL WULAN WINDY GENERAL HOSPITAL - Muhammad Adiul Ilham (SEAN Institute, 2022)
The main objective in this study was to determine the Relationship Analysis of Nurse Executor Behavior towards Completing the Inpatient Daily Census at Wulan Windy General Hospital. The research method used was quantitative with a cross sectional approach. The research location was at Windy Wulan General Hospital. The study population was all executive nurses in the inpatient unit at Wulan Windy General Hospital and a sample of 63 people. The results showed a variable relationship between knowledge, attitude, workload, and career development towards filling the daily census of hospitalization with p sig <0.05. It is expected for the general hospital wulan windy to do planning, controlling, evaluating the filling of the daily census carried out every day, providing continuous training and socialization about filling the inpatient daily census so as to get more professional paramedics, and it is expected for the hospital to be able to continue to provide opportunities for executive nurses to improve their careers, especially in the nursing field, in order to support their performance at work.